The influence of consumers’ trust and e-commerce platforms system quality on buying decision during Covid-19 pandemic - Choo, Yuen Theng; Kwan, Zhi Qian; Kwong, Cai Yan; Sum, Oi Ding; Yop, Jessie (2021)
The study concerns about the Covid-19 pandemic have shifted many businesses away from traditional (offline) models and toward modern (E-commerce) models, which has also shifted customers' purchasing platforms from physical to online. Trust in E-commerce platforms and satisfaction with their system quality influence customers' purchasing decisions in this situation. Individuals assume they are in control of their purchases, but there are some factors that influence them. As a result, this study sought to discover how consumer trust influences buying decisions on E-commerce platforms, as well as how system quality influences buying decisions on E-commerce platforms. As far as the researchers are aware, previous research has primarily focused on purchasing behaviour rather than purchasing decision; as a result, this study focuses on how the two variables mentioned above influence purchasing decision. An online survey was distributed to 330 respondents from various age groups in order to investigate the differences in perceived usefulness and perceived ease of use between age groups, as well as the influence of E-commerce platforms on consumer purchasing decisions (below 24, 25-44 and 45 and above etc.) The responses were analysed using multiple linear regression and the ANOVA test, respectively. The findings revealed few significant findings: the actual E-commerce platform use had a positive effect on purchasing decisions, and the perceived usefulness and ease of use of E-commerce platforms varies greatly depending on the age group as age group 45 and above differs greatly from the age groups 24 and below and 25 to 44. Furthermore, the systemic quality of E-commerce platforms has been demonstrated by using the TAM model to positively influence purchasing decisions. Consequently, public relations professionals can benefit from it as they can create more effective messages for their clients' audiences and more accurately target the potential audience as a result of the research.